224 RIGHT VENTRICULAR MECHANICS AND THE CLINICAL IMPLICATION OF 2D SPECKLE TRACKING ASSESSMENT IN SEVERE AORTIC STENOSIS. (15th December 2022) - Springhetti, Paolo; Ciceri, Luca; Urbani, Giulia; Dotto, Alberto; Maffeis, Caterina; Tafciu, Elvin; Bergamini, Corinna; Rossi, Andrea; Ribichini, Flavio; Benfari, Giovanni
Abstract: Introduction: The prognostic role of RV function assessment in severe AS has been demonstrated in previous studies. However, the role of 2D speckle tracking RV evaluation in the context of severe AS has not been completely clarified. Methods: We retrospectively evaluated consecutive patients with severe AS referred to TAVI at our institution. Exclusion criteria were severe aortic regurgitation, severe mitral stenosis and poor acoustic window for a correct 2D speckle tracking right chamber evaluation. The echocardiographic exams were analyzed off-line with a semi-automatic software (Tomtec Arena, Autostrain ®) to assess RVFW strain and LV GLS. Additionally, a conventional echocardiographic evaluation was made in both right and left chambers (LVEF, FAC, LVEF). Prevalence of conventional RV disfunction was defined as a TAPSE<17 mm or FAC<35%. RVFW impairment cuf-off was defined below 20%. Multivariate regression models were elaborate to assess the major determinants of RV function. Moreover, logistic regression analysis has been made to analyze if RV function could predict high-risk clinical features in the context of severe AS. Results: Our cohort was composed of 110 consecutive patients. Mean RVFW was 21±7%, TAPSE 21±4 mm, FAC 44±11% and mean RV area 10±4 cmq/mq. The prevalence of RV disfunction defined by standard echocardiography was 26% (29 patients), instead, RVFW was impaired (below 20%) in 53 patients (40%). At multivariate regression analysis, the main RVFW determinants were MR, AS severity, LVMI, GLS and E/e' (R2 0.68, p<0.001 including AVA; R2 0.53, p<0.001 including mean gradient). At logistic regression analysis RVFW strain was associated with previous HF hospitalization admission independently from TAPSE (CI 95% 1.03–1.22, p=0.008). Furthermore in a second model, RVFW strain was a significant predictor of advanced NYHA class independently from FAC (CI 95%, 1.01–1.18, p=0.0036). Conclusion: The major determinants of RV function in patients with severe AS were MR and LV function. A pressure overload driven by the MR-LV dysfunction combination on right sided heart could impact profoundly negatively on RV function. RVFW strain in this study resulted a more sensitive parameter that conventional RV assessment in highlighting more symptomatic severe-AS patients.